Dental orthodontic diaphragm and preparation method thereof

Through the methods of melt extrusion, hot pressing, rapid quenching and annealing, the problems of poor mechanical strength, insufficient transparency and safety of orthodontic membranes are solved, and a high-performance, low-cost orthodontic membrane suitable for invisible orthodontic treatment is prepared.

CN120620600APending Publication Date: 2025-09-12GRINM MEDICAL INSTR BEIJING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510979655.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-16
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Existing orthodontic diaphragms have problems such as poor mechanical strength, stress relaxation, high cost and safety. In particular, polypropylene materials are structurally unstable, lack transparency and may pose toxic risks when making dental molds.

Method used

Orthodontic membranes were prepared by melt extrusion, hot pressing, rapid quenching and annealing, with the cooling rate of rapid quenching controlled within the range of 50-150°C/min, cooling to below 90°C, and annealing at 80-150°C for 2-4h.

Benefits of technology

A dental orthodontic membrane with high mechanical strength, good transparency, excellent long-term stability and non-toxicity is prepared, which reduces material costs, improves production efficiency and product quality, and avoids the cost increase and toxicity risks caused by copolymerization modification or the addition of transparent nucleating agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005502555990000041
    Figure BDA0005502555990000041
  • Figure BDA0005502555990000051
    Figure BDA0005502555990000051
  • Figure BDA0005502555990000052
    Figure BDA0005502555990000052
Patent Text Reader

Abstract

The invention relates to the technical field of tooth orthodontic materials, and particularly discloses a preparation method of a tooth orthodontic diaphragm, which comprises the following steps: melt extrusion: pre-drying a polypropylene raw material, and then heating to 190-220 DEG C for melt extrusion; hot-press molding: carrying out hot-press molding on the material subjected to melt extrusion to obtain a hot-pressed diaphragm preform; rapid quenching: rapidly cooling the hot-pressed diaphragm preform to 90 DEG C or below at a rate of 50-150 DEG C / min; and annealing treatment: carrying out annealing treatment on the rapidly quenched hot-pressed diaphragm preform at 80-150 DEG C for 2-4 hours to obtain the tooth orthodontic diaphragm. According to the preparation method of the tooth orthodontic diaphragm provided by the invention, the tooth orthodontic diaphragm of which the tensile strength is greater than or equal to 25 MPa, the tensile modulus is greater than or equal to 1300 MPa, the tearing strength is greater than or equal to 180 MPa and the average grain size is 10-20 nm can be prepared, and the tooth orthodontic diaphragm can completely meet the requirements of orthodontic clinical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of orthodontic materials, and in particular to an orthodontic membrane and a preparation method thereof. Background Art

[0002] Invisible orthodontics, a correction technique that uses custom-made transparent braces to gradually adjust tooth alignment, has gained widespread popularity due to its aesthetic and comfort advantages. This correction method can reduce social awkwardness, facilitate oral hygiene, significantly reduce the risk of caries and periodontal disease, alleviate oral soft tissue irritation, reduce pain, and offer flexible follow-up appointments. Therefore, it meets the demands of modern society for improved quality of life and work efficiency, and has broad application prospects.

[0003] As a precision manufacturing technology for polymer material processing, the hot-pressed film forming process has demonstrated unique advantages in applications such as invisible braces, driving the development of invisible orthodontic technology towards higher precision and quality. In recent years, custom transparent braces used in invisible orthodontics have been produced using this process by processing thermoplastic films. Currently, commonly used thermoplastic film materials include polyethylene terephthalate (PET), polyethylene terephthalate-1,4-cyclohexanedimethanol (PETG), thermoplastic polyurethane (TPU), polycarbonate (PC), and polypropylene (PP). Polypropylene is increasingly used in dental molds due to its low price, excellent mechanical properties, and chemical stability. However, the use of polypropylene in dental molds still presents challenges such as structural instability, mechanical relaxation, and low transparency. While reports have suggested improving these issues through conventional copolymerization and the addition of transparent nucleating agents, these methods significantly increase the cost of the dental mold and may also introduce toxicity risks. Summary of the Invention

[0004] In order to overcome the problems of poor mechanical strength, stress relaxation, high cost and safety of existing orthodontic membranes, the present application provides an orthodontic membrane and a preparation method thereof.

[0005] In a first aspect, the present application provides a method for preparing an orthodontic diaphragm, which adopts the following technical solution: A method for preparing a tooth orthodontic membrane comprises the following steps: Melt extrusion: pre-dry the polypropylene raw material, then heat it to 190-220℃ for melt extrusion; Hot pressing molding: hot pressing the melt-extruded material to obtain a hot pressing film preform; Rapid quenching: Rapidly cool the hot pressed film preform to below 90°C at a rate of 50-150°C / min; Annealing treatment: annealing the hot-pressed membrane preform after rapid quenching at 80-150° C. for 2-4 hours to obtain the orthodontic membrane.

[0006] The present application provides a method for preparing a dental orthodontic diaphragm, which adopts the steps of melt extrusion, hot pressing, rapid quenching and annealing to prepare a dental orthodontic diaphragm with excellent mechanical strength, high transparency, good long-term stability and no toxic risks. Specifically: The present application uses a cold quenching process to make polypropylene spontaneously nucleate to form uniform and small crystal nuclei, thereby achieving a synergistic improvement in mechanical properties such as tensile strength and elongation at break; compared with the addition of nucleating agents in related technologies, the self-nucleating method does not have the problem of uneven dispersion of nucleating agents leading to fluctuations in optical properties and potential toxicity risks, and eliminates the step of adding nucleating agents, thereby reducing material costs. In addition, by further annealing the hot-pressed diaphragm preform after rapid quenching, the crystal structure can be stabilized, further improving the mechanical strength of the product and delaying stress relaxation. Compared with the methods in the related art, the preparation method of the orthodontic diaphragm provided in the present application can, on the one hand, effectively avoid the cost increase and toxicity problems caused by methods such as copolymerization modification or adding transparent nucleating agents. The prepared diaphragm can be used for invisible orthodontics, greatly reducing the treatment cost; on the other hand, it can also shorten the molding cycle, improve production efficiency and quality. The prepared orthodontic diaphragm has excellent mechanical properties, transparency and long-term use stability, and is suitable for orthodontic clinical applications.

[0007] In some embodiments, the cooling rate in the rapid quenching step can be 50-80°C / min, 50-100°C / min, 50-130°C / min, 50-150°C / min, 80-100°C / min, 80-130°C / min, 80-150°C / min, 100-130°C / min, 100-150°C / min or 130-150°C / min.

[0008] In a specific embodiment, the cooling rate in the rapid quenching step can be 50°C / min, 80°C / min, 100°C / min, 130°C / min or 150°C / min.

[0009] In some embodiments, the temperature after rapid quenching and cooling can be 5-15°C, 5-25°C, 5-50°C, 5-80°C, 15-25°C, 15-50°C, 15-80°C, 25-50°C, 25-80°C or 50-80°C.

[0010] In a specific embodiment, the temperature after rapid quenching and cooling can also be 80°C, 50°C, 25°C, 15°C or 5°C.

[0011] Optionally, the temperature of the hot pressing molding is 190-210° C. Optionally, the rapid quenching is water cooling or air cooling.

[0012] Optionally, the cooling rate in the rapid quenching step is 80-130°C / min.

[0013] Optionally, the temperature after rapid quenching is 5-80°C.

[0014] Optionally, the temperature after rapid quenching is 5-25°C.

[0015] Optionally, the annealing treatment is performed at a temperature of 100-140°C.

[0016] In this application, by annealing the hot-pressed diaphragm preform after hot pressing, the internal stress generated during the hot pressing process can be eliminated, allowing the polypropylene molecular chains to be better arranged and recrystallized, thereby refining the grain size. The refined grains can hinder dislocation movement, improve the tensile strength, tensile modulus and tear strength of the diaphragm, and thus improve the overall mechanical properties of the diaphragm. Through experimental research, this application found that by further controlling the temperature in the annealing step within the above range, the mechanical properties of the orthodontic diaphragm obtained are even better, with a tensile strength ≥35MPa, a tensile modulus ≥1450MPa, and a tear strength ≥190MPa.

[0017] In some embodiments, the annealing temperature may be 80-100°C, 80-120°C, 80-140°C, 80-150°C, 100-120°C, 100-140°C, 100-150°C, 120-140°C, 120-150°C, or 140-150°C.

[0018] In a specific embodiment, the annealing temperature may also be 80°C, 100°C, 120°C, 140°C or 150°C.

[0019] In some embodiments, the annealing treatment time may be 2-3 hours or 3-4 hours.

[0020] In a specific embodiment, the annealing treatment time can also be 2 hours, 3 hours or 4 hours.

[0021] Optionally, in the melt extrusion step, an antioxidant may be added to the melted material, mixed evenly, and then extruded using a mold.

[0022] In a second aspect, the present application also provides an orthodontic diaphragm prepared by the above-mentioned preparation method of the orthodontic diaphragm, wherein the orthodontic diaphragm has a tensile strength ≥ 25 MPa, a tensile modulus ≥ 1300 MPa, a tear strength ≥ 170 MPa, and a transmittance ≥ 90.0%.

[0023] In summary, this application has the following beneficial effects: 1. The present application provides a method for preparing a dental orthodontic diaphragm, which adopts the steps of melt extrusion, hot pressing, rapid quenching and annealing, and controls the cooling rate in the rapid quenching step within the range of 50-150°C / min, cools to below 90°C after rapid quenching, controls the annealing temperature within 80-150°C, and controls the annealing time within 2-4h. The prepared dental orthodontic diaphragm has excellent mechanical properties and transparency, with a tensile strength ≥25MPa, a tensile modulus ≥1300MPa, a tear strength ≥170MPa, and a transmittance ≥90.0%, which can fully meet the requirements of orthodontic clinical applications.

[0024] 2. This application further controls the cooling rate of rapid quenching within the range of 80-130°C / min, and the temperature after cooling is controlled within the range of 5-25°C. The obtained orthodontic membrane has better comprehensive performance in mechanical properties and transparency, with a tensile strength ≥28MPa, a tensile modulus ≥1330MPa, a tear strength ≥180MPa, and a transmittance ≥93.0%.

[0025] 3. The temperature in the further annealing step of the present application is controlled within the range of 100-140°C, and the annealing time is controlled within the range of 2-4h. The mechanical properties of the obtained orthodontic membrane are more excellent, with a tensile strength ≥35MPa, a tensile modulus ≥1360MPa, and a tear strength ≥190MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a flow chart of the method for preparing the orthodontic diaphragm provided in this application. DETAILED DESCRIPTION

[0027] The present application provides a method for preparing a dental orthodontic membrane, comprising the following steps: (1) Melt extrusion: pre-dry the polypropylene raw material, heat it to 190-220℃ to melt it, then add the antioxidant, mix it evenly, and extrude it through a mold; (2) Hot pressing: The melt-extruded material is hot pressed at 190-210°C by water cooling or air cooling to obtain a hot pressed film preform; (3) Rapid quenching: Rapidly cool the hot pressed film preform to below 90°C at a rate of 50-150°C / min; (4) Annealing treatment: The hot-pressed membrane preform after rapid quenching is annealed at 80-150° C. for 2-4 hours to obtain an orthodontic membrane.

[0028] In the present application, the model of polypropylene is PP R370Y, purchased from SK Global Chemical Yuplene of South Korea; the antioxidant is HD715MO produced by Borealis; and the raw materials used in the present application can all be obtained commercially.

[0029] The present application is further described in detail below with reference to the embodiments, performance testing and accompanying drawings.

[0030] Examples 1-9 Examples 1-9 respectively provide a method for preparing a dental orthodontic membrane.

[0031] The difference between the above embodiments is that the cooling rate in the rapid quenching step and the temperature after cooling are specifically shown in Table 1 below.

[0032] The method for preparing the orthodontic membrane provided in Examples 1-9 comprises the following steps: (1) Melt extrusion: pre-dry the polypropylene raw material, heat it to 210°C to melt it, then add the antioxidant, mix it evenly, and extrude it through a die; (2) Hot pressing: The melt-extruded material is hot pressed at 200°C by water cooling or air cooling to obtain a hot pressed film preform; (3) Rapid quenching: Rapidly cool the hot pressed film preform; the specific cooling rate and the temperature after cooling are shown in Table 1 below; (4) Annealing treatment: The hot-pressed membrane preform after rapid quenching is annealed at 80°C for 3 hours to obtain an orthodontic membrane.

[0033] Table 1 Rapid quenching cooling rate and temperature after cooling in the preparation method provided in Examples 1-9 Examples 10-15 Examples 10-15 respectively provide a method for preparing a dental orthodontic membrane.

[0034] The difference between the above embodiment and embodiment 3 lies in the temperature and time of the annealing treatment, as shown in Table 2 below.

[0035] Table 2 Temperature and time of annealing treatment in the preparation method of Examples 10-15 Comparative Example 1 Comparative Example 1 provides a method for preparing a dental orthodontic membrane.

[0036] The difference between the comparative example and Example 3 is that the cooling rate in the rapid quenching step is 20° C. / min.

[0037] Comparative Example 2 Comparative Example 2 provides a method for preparing a dental orthodontic membrane.

[0038] The difference between the comparative example and Example 3 is that the annealing temperature is 60° C. and the annealing time is 5 h.

[0039] Performance testing The mechanical properties and internal grain size of the orthodontic membranes obtained in Examples 1-15 and Comparative Examples 1-2 were tested, and the results are shown in Table 3 below.

[0040] (1) Mechanical properties: The tensile strength, tensile modulus and tear strength were tested according to the method of GB / T 1040.3 2006 Plastics - Determination of tensile properties; Type 5 specimens were used and the equipment tensile speed was set to 50 mm / min.

[0041] (2) Grain: Use XRD equipment to test and calculate the grain size according to the Scherrer formula.

[0042] (3) Transparency: Test according to the transmittance test method in GB / T 2410-2008 “Transparent plastics - Determination of light transmittance and haze”.

[0043] Table 3 Performance test results of orthodontic films obtained in Examples 1-5 and Comparative Examples 1-2 According to the test results in Table 3, the orthodontic membranes prepared in Examples 1-15 have a tensile strength of 26-36 MPa, a tensile modulus of 1318-1383 MPa, a tear strength of 177-196 MPa, an average grain size of 10.6-18.2 nm, and a transmittance of 90.2-94.7%; while the orthodontic membranes prepared in Comparative Examples 1-2 have a tensile strength of 21-24 MPa, a tensile modulus of 1213-1260 MPa, a tear strength of 158-161 MPa, an average grain size of 18.7-24.2 nm, and a transmittance of 86.5-89.4%. Therefore, it is explained that the present application adopts the steps of melt extrusion, rapid quenching, hot pressing and annealing, and controls the cooling rate in the rapid quenching step within the range of 50-150°C / min, the annealing temperature within 80-150°C, and the annealing time within 2-4h. The obtained orthodontic diaphragm has excellent mechanical properties and transparency, and can fully meet the requirements of orthodontic clinical applications.

[0044] From the test results of Examples 1-9, it can be seen that the tensile strength of the orthodontic membrane obtained in Example 1 and Examples 5-7 is 26-29 MPa, the tensile modulus is 1318-1327 MPa, the tear strength is 177-180 MPa, the average grain size is 10.6-18.2 nm, and the transmittance is 90.2-94.3%; while the tensile strength of the orthodontic membrane obtained in Examples 2-4 and Examples 8-9 is 28-32 MPa, the tensile modulus is 1335-1344 MPa (≥1330 MPa), the tear strength is 181-184 MPa (≥180 MPa), the average grain size is 12.7-15.5 nm (≤16.0 nm), and the transmittance is 93.5-94.7% (≥93.0%). Therefore, it is shown that the present application further controls the cooling rate of rapid quenching within the range of 80-130°C / min, and the temperature after cooling within the range of 5-25°C, and the obtained orthodontic membrane has better comprehensive performance in mechanical properties and transparency.

[0045] From the test results of Example 3 and Examples 10-15, it can be seen that the tensile strength of the orthodontic membrane obtained in Example 3 and Example 13 is 30-33 MPa, the tensile modulus is 1335-1341 MPa, the tear strength is 184-187 MPa, the average grain size is 13.3-13.4 nm, and the transmittance is 94.2-94.3%; while the tensile strength of the orthodontic membrane obtained in Examples 10-12 and Examples 14-15 is 35-36 MPa (≥35 MPa), the tensile modulus is 1369-1383 MPa (≥1360 MPa), the tear strength is 191-196 MPa (≥190 MPa), the average grain size is 12.8-13.3 nm (≤14.0 nm), and the transmittance is 94.3-94.4% (≥94.0%). Therefore, it is shown that the present application further controls the temperature in the annealing step within the range of 100-140°C and the annealing time within the range of 2-4h, and the mechanical properties of the prepared orthodontic membrane are even better.

[0046] Although the present invention has been described in detail above using general descriptions and specific embodiments, it will be apparent to those skilled in the art that modifications and improvements may be made based on the present invention. Therefore, such modifications and improvements, which do not depart from the spirit of the present invention, are intended to be within the scope of protection claimed herein.

Claims

1. A method for preparing a dental orthodontic membrane, characterized in that: The following steps are involved: Melt extrusion: pre-dry the polypropylene raw material, then heat it to 190-220℃ for melt extrusion; Hot pressing molding: hot pressing the melt-extruded material to obtain a hot pressing film preform; Rapid quenching: Rapidly cool the hot pressed film preform to below 90°C at a rate of 50-150°C / min; Annealing treatment: annealing the hot-pressed membrane preform after rapid quenching at 80-150° C. for 2-4 hours to obtain the orthodontic membrane.

2. The method for preparing an orthodontic diaphragm according to claim 1, wherein: The rapid quenching adopts water cooling or air cooling.

3. The method for preparing an orthodontic diaphragm according to claim 1, wherein: The cooling rate in the rapid quenching step is 80-130°C / min.

4. The method for preparing an orthodontic diaphragm according to claim 1, wherein: The temperature after the rapid quenching is 5-80°C.

5. The method for preparing an orthodontic diaphragm according to claim 1, wherein: The temperature after the rapid quenching is 5-25°C.

6. The method for preparing an orthodontic diaphragm according to claim 1, wherein: The temperature of the annealing treatment is 100-140°C.

7. The method for preparing an orthodontic diaphragm according to claim 1, wherein: In the melt extrusion step, an antioxidant may be added to the melted material, mixed evenly, and then extruded using a mold.

8. The orthodontic membrane prepared by the method for preparing an orthodontic membrane according to any one of claims 1 to 7, characterized in that: The orthodontic membrane has a tensile strength of ≥25 MPa, a tensile modulus of ≥1300 MPa, a tear strength of ≥170 MPa, and a light transmittance of ≥90.0%.